2016
DOI: 10.4995/eurocall.2016.5693
|View full text |Cite
|
Sign up to set email alerts
|

Variations in motivation, anxiety and boredom in learning English in Second Life

Abstract: The article presents the results of a study whose main aim was to investigate the changes in motivation, language anxiety and boredom in learning English in Second Life. The sample consisted of 16 second year students of English philology. The study was conducted over the period of a summer semester. During that time the participants in the study were asked to use Second Life and practice English there in their own time. The data were obtained by means of a background questionnaire and session logs and subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 26 publications
(21 reference statements)
2
28
0
3
Order By: Relevance
“…The findings demonstrated that the intervention had a limited impact on lowering FLA among the treatment participants, although it made them less anxious with regard to communication apprehension. Another study (Kruk 2016b) examined fluctuations in the self-reported levels of FLA, along with motivation and boredom, by a group of 16 English majors during their visits to SL over the period of one semester. The findings showed a successive increase in the levels of motivation and boredom, while those of FLA remained quite stable over time.…”
Section: Dynamics Of Fla In Traditional Contexts and Vwsmentioning
confidence: 99%
“…The findings demonstrated that the intervention had a limited impact on lowering FLA among the treatment participants, although it made them less anxious with regard to communication apprehension. Another study (Kruk 2016b) examined fluctuations in the self-reported levels of FLA, along with motivation and boredom, by a group of 16 English majors during their visits to SL over the period of one semester. The findings showed a successive increase in the levels of motivation and boredom, while those of FLA remained quite stable over time.…”
Section: Dynamics Of Fla In Traditional Contexts and Vwsmentioning
confidence: 99%
“…Graham, Courtney, Tonkyn, and Marinis (2016) reported that adolescents valued learning French as L2 for travel and communication; their self-confidence and progress expectations, however, gradually decreased. Thus, the English classroom should include practical sessions during which students would communicate in English (Al-Qahtani, 2013) and utilize digitalized technology activities, such as reading stories online (Hsin-Chou, 2013) and virtual world gaming (Kruk, 2016b), which they use in their everyday life. The perceived freedom of choice and personal competence correlate with more self-determined forms of motivation (Noels et al, 2003), as learners employ cognitive, meta-cognitive, and social language learning strategies (Al-Qahtani, 2013).…”
Section: Motivation To Learn Foreign Languages In Children Adolescenmentioning
confidence: 99%
“…Other researchers took students affective factors as their focus, e.g. Kruk who investigated the variations in motivation, anxiety and boredom in learning English in Second Life [21]; Suherdi investigated ways of helping students as digital native in developing effective learning [22], and Suherdi and Ihrom investigated students' motivation, ownership, and achievement through YouTube video maker [23].…”
Section: Introductionmentioning
confidence: 99%